Kebijakan dan Implementasi Manajemen Pendidikan Tinggi dalam Meningkatkan Mutu Pendidikan - Sri Winarsih (Cendekia: Kependidikan dan Kemasyarakatan, 2017)
In improving the quality of education, there should be sustainability of performance and quality improvement. The sustainable quality improvement serves as the measure to overcome the problems of low quality education which rely on conventional approaches. The quality assurance approach leads higher education institutions to learn and implement Total Quality Management (TQM). TQM is an integrated quality management undertaken by every level of managementand all units within the organizational system which aims at providing satisfactory service to the customer. So every Higher Education should optimize management to improve quality. There are four successful scopes of higher educationmanagement, such as: (1) students are satisfied with the higher education services; (2) educational customersare satisfied with the service to its students; (3) stake holders are satisfied to have graduates with high quality and meet theexpectation; (4) lecturers and staff are satisfied with the services of higher education in some areas: division of labor, relationships and communication between lecturers/leaders, employees, salary/honor received and service.في مجال ترقية جودة التربية والتعليم يُحتاج إلى ترقية روح العمل وتحسين الجودة المستمر. بهذا التحسين المستمرّ يُرجى أن يكون حلا لانخفاض جودة التربية والتعليم التى لا تعتمد فقط على المدخل التقليدي.  فالتوجه إلى ترقية الجودة تقتضي مؤسسات التعليم العالي معرفة وتطبيق Total Quality Management (TQM). هذه الطريقة كأداة للتنسيق المتحد للجودة التي قام بها كل فرع إداري في المنظّمة بهدف تقديم  أحسن الخدمات للأعضاء والناس. لذا فإن التعليم العالي لابد من تفعيل جانب الإدارة لترقية الجودة. وثمة أمور أربعة يتعلق بها نجاح التنسيق للتعليم العالي : 1)  قناعة طلاب الجامعة بما قدّمه التعليم العالي، 2) قناعة المجتمع بما قدّمه التعليم العالي لطلابه، 3) قناعة المجتمع المستوظفين لخرّجي التعليم العالي، 4) قناعة المحاضرين والموظّفين بما قدّمه التعليم العالي في صورة تقسيم العمل، والتواصل والتعامل فيما بين منسوبي التعليم العالي والموظّفين، وجانب الراتب الشهري والخدمات.